Synthesis of carbon nanotubes-mesostructured silica nanoparticles composites for adsorption of methylene blue - Karim, Ainul Hakimah (2015)
The mesostructured silica nanoparticles (MSN) have been widely developed for the removal of various pollutants due to their highly porous structure and other novel features. While carbon nanotubes (CNT) are attracting great interest owing to its large specific surface area, small size, hollow and layered structures. The integration of these outstanding properties by modification of MSN with singlewalled CNT (SWCNT) and multiwalled CNT (MWCNT) is quite new in this area of study and is expected to produce an adsorbent with higher adsorption capacity. In this study, three types of adsorbents were prepared by a simple one step method; MSN, series of SWCNT-MSN composites, and series of MWCNT-MSN composites. Their characteristics have been observed by XRD, N2 physisorption, FTIR, TEM, and FESEM, while their adsorption performance were evaluated on the adsorption of methylene blue (MB) at various pH, adsorbent dosage, initial MB concentration, and temperature. The results demonstrated that the adsorbents were prepared with mesoporous structures and produces relatively higher number of pores with larger diameters. The CNTs were found to improve the physicochemical properties of the MSN and led to an enhanced adsorptivity for MB. N2 physisorption measurements revealed the development of a bimodal pore structure in MWCNT-MSN composites that increased the pore size, pore volume and surface area. The best conditions for MSN, SWCNT-MSN and MWCNT-MSN composites achieved at pH 7 and 303 K using 0.05 g L-1 adsorbent and 100 mg L-1 MB. Fitting with linear Langmuir isotherm produce the maximum adsorption capacity of 500.1 mg g-1, 500.0 mg g-1, and 263.2 mg g-1 for MSNAP, SWCNT-MSN and MWCNT-MSN, respectively. The equilibrium data were evaluated using the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherm models, with the Freundlich model affording the best fit to the adsorption data for MSN and Langmuir model for both SWCNT-MSN and MWCNT-MSN. The adsorption kinetics for all MSN, SWCNT-MSN and MWCNT-MSN were best described by the pseudo-second order model. Thermodynamic study showed that the nature of MSNs and MWCNT-MSNs are exothermic, and endothermic for SWCNT-MSNs. This study is proven to produce a relatively new and potential mesostructured materials used as adsorbent for dye removal and water treatment.